A comparative evaluation of coenzyme Q10-loaded liposomes and solid lipid nanoparticles as dermal antioxidant carriers - Gokce EH (Dove Medical Press, 2012)
Evren H Gokce,1 Emrah Korkmaz,1 Sakine Tuncay-Tanriverdi,1 Eleonora Dellera,2 Giuseppina Sandri,2 M Cristina Bonferoni,2 Ozgen Ozer11Department of Pharmaceutical Technology, Faculty of Pharmacy, University of Ege, Izmir, Turkey; 2Department of Drug Sciences, University of Pavia, Pavia, ItalyBackground: The effective delivery of coenzyme Q10 (Q10) to the skin has several benefits in therapy for different skin pathologies. However, the delivery of Q10 to deeper layers of skin is challenging due to low aqueous solubility of Q10. Liposomes and solid lipid nanoparticles (SLN) have many advantages to accomplish the requirements in topical drug delivery. This study aims to evaluate the influence of these nanosystems on the effective delivery of Q10 into the skin.Methods: Q10-loaded liposomes (LIPO-Q10) and SLNs (SLN-Q10) were prepared by thin film hydration and high shear homogenization methods, respectively. Particle size (PS), polydispersity index (PI), zeta potential (ZP), and drug entrapment efficiency were determined. Differential scanning calorimetry analysis and morphological transmission electron microscopy (TEM) examination were conducted. Biocompatibility/cytotoxicity studies of Q10-loaded nanosystems were performed by means of cell culture (human fibroblasts) under oxidative conditions. The protective effect of formulations against production of reactive oxygen species were comparatively evaluated by cytofluorometry studies.Results: PS of uniform SLN-Q10 and LIPO-Q10 were determined as 152.4 ± 7.9 nm and 301.1 ± 8.2 nm, respectively. ZPs were −13.67 ± 1.32 mV and −36.6 ± 0.85 mV in the same order. The drug entrapment efficiency was 15% higher in SLN systems. TEM studies confirmed the colloidal size. SLN-Q10 and LIPO-Q10 showed biocompatibility towards fibroblasts up to 50 µM of Q10, which was determined as suitable for cell proliferation. The mean fluorescence intensity % depending on ROS production determined in cytofluorometric studies could be listed as Q10 ≥ SLN-Q10 > LIPO-Q10.Conclusion: The LIPO-Q10 system was able to enhance cell proliferation. On the contrary, SLN-Q10 did not show protective effects against ROS accumulation. As a conclusion, liposomes seem to have advantages over SLN in terms of effective delivery of Q10 to skin for antioxidant purposes.Keywords: solid lipid nanoparticles, liposomes, coenzyme Q10, antioxidant, cytotoxicity